Thoraco-laparotomy approach to salvage a life-threatening cardiac box stab injury to the infecrior vena cava in Malaysia: a case report - Ida Arinah Mahadi; Jih Huei Tan; Jin Zhe Teh; Yuzaidi Mohamad; Imran Alwi Rizal (Journal of Trauma and Injury)
Torso stab injuries near the cardiac box may present unique challenges due to difficulties in hemorrhage control. For a stab injury to the heart, the repair is straightforwardly performed via median sternotomy. In contrast, injuries to the inferior vena cava are challenging to repair, especially when they are close to the diaphragm, and the bleeding can be torrential. Herein, we describe a case of a self-inflicted stab wound within the "cardiac box." The trajectory of the stab injuries went below the diaphragm and injured the infradiaphragmatic inferior vena cava. Successful emergent repair via the thoraco-laparotomy approach revived the young man. In this report, we revisit and discuss previous large series of patients with this rare vena cava injury.